Welcome! : English for the travel and tourism industry : student's book - Jones, Leo. (Cambridge, U.K ; Melbourne, Vic. : Cambridge University Press, 1998)
Different kinds of people. International travel. Phone calls. Food and drink. Letters and faxes. Accomodation. Money. Travelling around. Problems. Attractions and activities.
Keywords: English language; Foreign speakers; English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; Tourism -- Language